Evaluation of Impact of Interferon-Induced Helicase C Domain-Containing Protein 1 Gene in Egyptian Systemic Lupus Erythematosus Patients and its Relationship With Vascular Manifestations of the Disease - Sahar NASSEF,; Mervat ESSAM,; Dina ABDELFATTAH,; Doaa ELSEHEMY,; Sahar ABOUELEZZ, (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate the impact of interferon-induced helicase C domain-containing protein 1 (IFIH1) gene single nucleotide polymorphism on interferon pathway signaling in systemic lupus erythematosus (SLE) patients specifically with vascular affection. Patients and methods: The cross-sectional study included 30 consecutive SLE patients (2 males, 28 females; mean age 28±3.4 years; range 16 to 40 years) diagnosed according to the American College of Rheumatology revised criteria and 10 healthy age- and sex-matched controls (2 males, 8 females; mean age 27±2.5 years; range 22 to 23 years). SLE patients and controls were compared in terms of quantitative reverse transcriptase polymerase chain reaction gene expression of IFIH1 gene, von Willebrand factor, carotid intima-media thickness, and ankle brachial index. Results: Interferon-induced helicase C domain-containing protein 1 gene expression was significantly higher in SLE patients than controls (1.7±0.6 and 0.5±0.2, respectively) (p<0.0001). IFIH1 gene expression was highly related to vascular complication with a cutoff point at 1.74 and it positively correlated with other endothelial dysfunction markers. Conclusion: Interferon-induced helicase C domain-containing protein 1 gene (single nucleotide polymorphism 1990670) is associated with SLE in Egyptian patients. Expression of IFIH1 gene is related to disease activity and may serve as a novel predictor of vascular affection in SLE.